The Effect of Child Care and Part Time Opportunities on Participation and Fertility Decisions in Italy - Daniela Del Boca (Institute for the Study of Labor (IZA), 2002)
Economic models of household behavior typically yield the prediction that increases in schooling levels and wage rates of married women lead to increases in their labor supply and reductions in fertility. In Italy, as well as in other Southern European countries, low labor market participation rates of married women are observed together with low birth rates. Our proposed explanation for this apparent anomaly involves the Italian institutional structure, particularly as reflected in rigidities and imperfections in the labor market and characteristics of the publicly-funded child care system. These rigidities tend to simultaneously increase the costs of having children and to discourage the labor market participation of married women. We analyze a model of labor supply and fertility, using panel data from the Bank of Italy which have been merged with regional data describing the available opportunities in each sample household?s environment. The empirical results show that the availability of child care and part time work increase both the probability of working and having a child. Policies which would provide more flexible working hours choices and greater child care availability would aid in reducing the financial burden of children.
Keywords: J2; D1; C3; 330; Labor market decisions; fertility; child care; Frauenerwerbstätigkeit; Arbeitsangebot; Familienökonomik; Teilzeitarbeit; Kinderbetreuung; Schätzung; Theorie; Italien